Idiosyncratic risk and volatility bounds, or can models with idiosyncratic risk solve the equity premium puzzle? - Martin Lettau (Federal Reserve Bank of New York, 2001)
This paper uses Hansen and Jagannathan's (1991) volatility bounds to evaluate models with idiosyncratic consumption risk. I show that idiosyncratic risk does not change the volatility bounds at all when consumers have CRRA preferences and the distribution of the idiosyncratic shock is independent of the aggregate state. Following Mankiw (1986), I then show that idiosyncratic risk can help to enter the bounds when idiosyncratic uncertainty depends on the aggregate state of the economy. Since individual consumption data are not reliable, I compute an upper bound of the volatility bounds using individual income data and assume that agents have to consume their endowment. I find that the model does not pass the Hansen and Jagannathan test even for very volatile idiosyncratic income data.
Keywords: E44; G11; G12; 330; idiosyncratic risk; risk premia; volatility bounds; asset prices; incomplete markets; Capital Asset Pricing Model; Risiko; Risikoprämie; Volatilität; Verbraucherausgaben; Theorie